Mie Krill: Incorporation of Indigenous Udang Saih (Sumatran Krill) Extract Containing Astaxanthin and Essential Fatty Acids into an Instant Noodle Product Made from Composite Flour - Gunawan, Hanz A.S.; Kurniawan, Jovine M.; Sudarsono, Edwina V.; Effendi, Jonathan; Heriyanto, Heriyanto (Indonesian Journal of Natural Pigments, 2021)
Indonesia is an archipelagic country. One can be found as the indigenous specimen alongside the coastal part of the country is the Sumatran Krill (SK), commonly known as ‘Udang Saih’ which can be found in Padang, West Sumatra. While the local people use it to make traditional condiment (like shrimp paste), the krill itself could be extracted to create more valuable products since it contains various important unsaturated fatty acids such as omega-3, omega-6, omega-7, and omega-9 and the powerful antioxidant carotenoid named astaxanthin. Astaxanthin as the main carotenoid in SK extract offers several health benefits such as anti-inflammatory properties, support immune system modulation, as well as maintaining brain, cardiovascular, and eye health. In this study, we aim to incorporate the SK extract into an instant noodle product. In addition, we used the composite flours consisted of high-protein wheat flour (WF) and yellow sweet potato flour (YSPF) which are rich in β-Carotene as a vitamin A precursor, to further enhance its eye health property. The instant noodle prototype (M2) was made from a mixture of YSPF (40 g), WF (40 g), super-concentrated astaxanthin in sunflower oil (8 mL), and super-concentrated astaxanthin (2.4 mL) had the highest score of sensory attributes. This instant noodle prototype was claimed to contain astaxanthin, essential fatty acids, and provitamin A carotenoid as well as low in gluten content. Therefore, this instant noodle prototype is believed to increase the health benefits and can be well accepted in society.